Intracellular Delivery of a Planar DNA Origami Structure by the Transferrin‐Receptor Internalization Pathway. Issue 19 (31st March 2016) - Schaffert, David H.; Okholm, Anders H.; Sørensen, Rasmus S.; Nielsen, Jesper S.; Tørring, Thomas; Rosen, Christian B.; Kodal, Anne Louise B.; Mortensen, Michael R.; Gothelf, Kurt V.; Kjems, Jørgen
Abstract : DNA origami provides rapid access to easily functionalized, nanometer‐sized structures making it an intriguing platform for the development of defined drug delivery and sensor systems. Low cellular uptake of DNA nanostructures is a major obstacle in the development of DNA‐based delivery platforms. Herein, significant strong increase in cellular uptake in an established cancer cell line by modifying a planar DNA origami structure with the iron transport protein transferrin (Tf) is demonstrated. A variable number of Tf molecules are coupled to the origami structure using a DNA‐directed, site‐selective labeling technique to retain ligand functionality. A combination of confocal fluorescence microscopy and quantitative (qPCR) techniques shows up to 22‐fold increased cytoplasmic uptake compared to unmodified structures and with an efficiency that correlates to the number of transferrin molecules on the origami surface. Abstract : The uptake of a transferrin‐loaded 2D DNA origami structure into a cancer cell line correlates with the number of transferrin molecules on the structure. This may be used to enhance cell uptake of DNA nanostructures currently being harnessed as smart molecular vehicles in drug delivery.